2012
DOI: 10.12659/msm.882717
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial bridging is a potential risk factor of very late stent thrombosis of drug eluting stent

Abstract: SummaryDrug eluting stents have been implanted worldwide and used in nearly 90% of percutaneous coronary interventions in China. Although many randomized trials have confirmed the efficacy and safety profile of drug eluting stents, they were not powered to detect or exclude the effect of drug eluting stents on rare events such as stent thrombosis. Several mechanisms of very late stent thrombosis have been postulated, but are not widely accepted. Virchow’s triad describes the 3 main factors of thrombus formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…24) Jiang reported that MB is a potential risk factor of stent thrombosis. 25,26) In our study, there was one case with acute intrastent thrombosis that was diagnosed 4 h after PCI in the MB group. We considered that the periodical pressing of MB, which leads to distinct hemodynamic changes and critical endothelial injuries, may play an important role in stent thrombosis.…”
Section: Discussionmentioning
confidence: 57%
“…24) Jiang reported that MB is a potential risk factor of stent thrombosis. 25,26) In our study, there was one case with acute intrastent thrombosis that was diagnosed 4 h after PCI in the MB group. We considered that the periodical pressing of MB, which leads to distinct hemodynamic changes and critical endothelial injuries, may play an important role in stent thrombosis.…”
Section: Discussionmentioning
confidence: 57%
“… 1 Stent implantation may rectify the abnormal hemodynamics in patients with flow-limiting plaque but with concerns on perforation during stent deployment, stent fracture, 4 in-stent restenosis, 5 and stent thrombosis. 6 However, it may not be possible to avoid these interventional complications, especially when the target lesion is located at the MB segment. DCB could inhibit smooth muscle cell proliferation and thus eliminate stent thrombosis and reduce restenosis by directly contacting the antiproliferative drug with the vessel wall by a semicompliant balloon.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular imaging (e.g., IVUS) during coronary angiography may provide additional assistance in the recognition of plaque location and its spatial relationship with MB 1. Stent implantation may rectify the abnormal hemodynamics in patients with flow-limiting plaque but with concerns on perforation during stent deployment, stent fracture,4 in-stent restenosis,5 and stent thrombosis 6. However, it may not be possible to avoid these interventional complications, especially when the target lesion is located at the MB segment.…”
mentioning
confidence: 99%
“…Therefore, clinical features may manifest as angina-like chest pain, coronary spasm, acute coronary syndromes, left ventricular dysfunction, ventricular arrhythmias, and even sudden cardiac death. [42][43][44][45][46][47][48][49] Serious cardiac events are not common in the clinical setting. In addition, it is still arguable and uncertain whether MB can be directly attributable as the cause of the events.…”
Section: Clinical Features and Diagnostic Managementmentioning
confidence: 99%